Studi Pengaruh Perubahan Kedalaman Saluran terhadap Pengelolaan Sedimen di Saluran Box Culvert - Angela Jasmine Tanya Tjahyana; Umboro Lasminto (Jurnal Teknik Sipil, 2020)
The most frequent problem that occurred in a box culvert is sedimentation. Sediments can be transported by changes in the water flow velocity, which can be influenced by changes of depth, h, of the channel bed. This research studies the change in h1 to h2 = 1,1 h1, 1,3 h1, 1,5 h1, 1,8 h1, and 2 h1, by simulation using SSIIM 1 program. The graph of the grain size distribution shows that the sediment consists of 99% of sands and 1% of silt, which its diameter of d50 = 0.8 mm and d90 = 4 mm. The discharge is 0.328 m3/s. The results, the deeper of the bed channel changes, the slower the flow velocity. The bed shear stress in changing the bed channel is smaller than the critical bed shear stress, and it makes the sediment stays. Based on the results, the variation of h2 = 1,1 h1, is preferred in sediment management.